Calculation of the Optimal Doses of the Ameliorant Neutralizing Heavy Metals in Anthropogenically Polluted Soils - Tamoyan, S. J. (ՀԱԱՀ հիմնադրամ)
The paper considers improvement ways of the technology for neutralizing soil polluting heavy metals. The common technologies do not yet specify the effective and environmentally friendly application doses of ameliorants absorbing the pollutants. The theoretical calculations have proved that there is a quantitative relationship between the sizes of different fractions contained in the ameliorant and the optimal share of the ameliorant, in accordance wih the level of soil pollution. The derived relation enables to calculate the optimal shares of the ameliorants absorbing heavy metals in soil.
Keywords: Agronomy and Agroecology